Depressed-Type Colonic Lesions and "De Novo" Cancer in Familial Adenomatous Polyposis: A Colonoscopist's Viewpoint. (27th February 2013) - Kudo, Shin-ei; Sugihara, Yuusaku; Kida, Hiroyuki; Ishida, Fumio; Miyachi, Hideyuki; Mori, Yuichi; Misawa, Masashi; Hisayuki, Tomokazu; Kodama, Kenta; Wakamura, Kunihiko; Hayashi, Takemasa; Wada, Yoshiki; et al.
Abstract : Familial adenomatous polyposis (FAP) is the most common inherited polyposis syndrome. Almost all patients with FAP will develop colorectal cancer if their FAP is not identified and treated at an early stage. Although there are many reports about polypoid lesions and colorectal cancers in FAP patients, little information is available concerning depressed lesions in FAP patients. Several reports suggested that depressed-type lesions are characteristic of FAP and important in the light of their rapid growth and high malignancy. Here, we describe the occurrence of depressed-type lesions in FAP patients treated at our institution. Between April 2001 and March 2010, eight of 18 FAP patients had colorectal cancers. Depressed-type colorectal cancer was found in three patients. It should be kept in mind that depressed-type lesions occur even in FAP.